Mapping carbon nanotube orientation by fast fourier transform of scanning electron micrographs - Brandley,E; Greenhalgh,E; Shaffer,M; Li,Q (Carbon, 2018)
A novel method of applying a two-dimensional Fourier transform (2D-FFT) to SEM was developed to map the CNT orientation in pre-formed arrays. Local 2D-FFTs were integrated azimuthally to determine an orientation distribution function and the associated Herman parameter. This approach provides data rapidly and over a wide range of lengthscales.Although likely to be applicable to a wide range of anisotropic nanoscale structures, the method was specifically developed to study CNT veils, a system in which orientation critically controls mechanical properties. Using this system as a model, key parameters for the 2D-FFT analysis were optimised, including magnification and domain size; a model set of CNT veils were pre-strained to 5%, 10% and 15%, to vary the alignment degree. The algorithm confirmed a narrower orientation distribution function and increasing Herman parameter, with increasing pre-strain.To validate the algorithm, the local orientation was compared to that derived from a common polarised Raman spectroscopy. Orientation maps of the Herman parameter, derived by both methods, showed good agreement. Quantitatively, the mean Herman parameter calculated using the polarised Raman spectroscopy was 0.42±0.004 compared to 0.32±0.002 for the 2D-FFT method, with a correlation coefficient of 0.73. Possible reasons for the modest and systematic discrepancy were discussed.